Prospects of long-term development of Shebelynka gas-condensate deposit in conditions of stocks recovery - Фик, Ілля Михайлович; Фик, Михайло Ілліч; Фик, Ілля Михайлович (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
The work is aimed to study the gas recovery stabilization prospects in Ukraine on the existing deposits due to renewable processes concerning gas reserves. The article reviews and analyzes the main results in the Shebelynka gas condensate field (GCF) development from the point of view of its water flooding.It is possible to restore the gas reserves in the assumption that they are being developed due to the gas flow from deep horizons. In detail, all factors are taken into consideration, which influences the formation pressure in the process of deposits development. The work presents analysis of the water pressure system in the Shebelinka GCF, the results of the calculation of reserves of edge water (water pressure system of the field is limited), investigates the dynamics of water flooding (intrusion of water in gas deposits) and the role of capillary forces in slowing down the advance of the water front. It was shown that water flooding practically does not affect the development of gas depletion, and the reservoir pressure-decline rate is slowing down both under the influence of known factors and due to the flow of gas through tectonic disruptions, especially in the core deposit. It is proved that when the annual gas consumption is reduced to 1800-1900 million 3, it will be fully compensated by the crossflow of gas. The graphic forecast of gas recovery till 2040 is presented in variants without compressor and compressor opening since 2019, taking into consideration the reserves stock.It has been calculated that with introduction of the planned new compressor station at Shebelinka GCF annual gas production in the period of 2020-2040 will be maintained at 2.4-2.1 billion cubic meters and additional gas extraction for the period 2019-2036 is - 6.5 billion m3.During the development of the field, depression between the main reservoir and the deep horizons of carbon will increase, that might increase the volume of gas crossflow and accelerate the degassing of the Earth, taking into account presence of macro- and micro-tectonic faults.Considering the possibility of a long-term development in the Shebelinka GCF, it is necessary to pay special attention to the fund of wells, its updating, repair or use as a means for receiving the heat from the Earth.The phenomenon of restoration of gas reserves at the Shebelinka GCF, which was established by researches, is promising for other deposits of Ukraine and needs further special researches, on separate objects.Object of research: Shebelinka gas condensate field. Gas extraction and processes for maintaining reservoir pressure, including through the gas crossflow of gas from the deep horizons of tectonic disturbances.Subject of the study: Analysis and forecast of gas production in the future for various options for development, both compressor and non-compressor exploitation of the deposit, taking into consideration maintenance of reservoir pressure and stock reserves.